2019
DOI: 10.1055/a-0923-8215
|View full text |Cite
|
Sign up to set email alerts
|

Plant Latex, from Ecological Interests to Bioactive Chemical Resources

Abstract: Historically, latex-bearing plants have been regarded as important medicinal resources in many countries due to their characteristic latex ingredients. They have also often been endowed with a social or cultural significance in religious or cult rituals or for hunting. Initial chemical studies focused on the protein or peptide content but recently the interest extended to smaller molecules. Latex has been found to contain a broad range of specialized metabolites such as terpenoids, cardenolides, alkaloids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 141 publications
1
15
0
2
Order By: Relevance
“…Plant latex contains a wide range of specialized metabolites that are partially responsible for various activities, such as antibacterial, antifungal and anthelmintic activities; among these compounds are terpenoids, cardenolides, alkaloids and phenolics (Abarca et al, 2019). In C. procera latex, several metabolites have been identified, including cardenolides, alkaloids, steroids and phenols (Chundattu et al, 2016;Mohamed et al, 2015;Ranjit et al, 2012), which were also found in the present investigation.…”
Section: Discussionsupporting
confidence: 81%
“…Plant latex contains a wide range of specialized metabolites that are partially responsible for various activities, such as antibacterial, antifungal and anthelmintic activities; among these compounds are terpenoids, cardenolides, alkaloids and phenolics (Abarca et al, 2019). In C. procera latex, several metabolites have been identified, including cardenolides, alkaloids, steroids and phenols (Chundattu et al, 2016;Mohamed et al, 2015;Ranjit et al, 2012), which were also found in the present investigation.…”
Section: Discussionsupporting
confidence: 81%
“…The chemical composition of latexes includes three major categories of compounds: polyisoprene polymers (rubber), proteins, and low molecular weight specialized metabolites (Salomé-Abarca et al 2019). Among these, proteins have been relatively more studied due to their evident biological functions against herbivores and pathogens (Konno 2011;Ramos et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several triterpenoids have been identified in Euphorbia species (Mahlberg and Pleszczynska 1983;Ponsinet and Ourisson 1968) and many of them have been suggested to be chemomarkers for certain taxons (Mahlberg et al 1987;Mahlberg et al 1988). Moreover, references show rubber and triterpenes as the main components of rubbery latexes independently of the latex plant-bearing species (Agrawal and Konno 2009;Konno 2011;Ramos et al 2019;Salomé-Abarca et al 2019). Also, it has been proposed that given their proximity in biosynthetic pathways, their coexistence in laticifers might have occurred during evolution (Mahlberg 1985;Nemethy et al 1983;Piazza et al 1987a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Os vegetais podem liberar seus metabólitos por mecanismos estratégicos, conhecidos como exsudados, seja na forma de óleo essencial, goma, resina ou látex (Abarca et al, 2019). Esse último exsudado pode apresentar atividades biológicas variadas, pois sua composição é frequentemente rica em ácidos graxos, hidrocarbonetos, carboidratos, proteínas e metabólitos secundários Silva et al, 2018;D'Abaia et al, 2020).…”
Section: Introductionunclassified